Fatigue Design Research on Notch–Stud Connectors of Timber–Concrete Composite Structures - Zuen Zheng; Shuai Yuan; Guojing He (Buildings)
To investigate the mechanical behavior and damage mechanism of notch–stud connectors in timber–concrete composites under fatigue loading, fifteen push-out specimens in five groups were designed with load cycles as the key variable. Fatigue failure modes and mechanisms were analyzed to examine fatigue life, stiffness degradation, and cumulative damage laws of connectors. Numerical simulations with up to 100 load cycles explored timber/concrete damage effects on stud fatigue performance. Based on the results, an S-N curve was established, a fatigue damage model developed, and a fatigue design method proposed for such connectors. Primary failure modes were stud fracture and local concrete crushing in notches. Stiffness degradation followed an inverted “S”-shaped “fast–slow–fast” pattern. Using residual slip as the damage variable, a two-stage fatigue damage evolution model was constructed from the damage–cycle ratio relationship, offering a new method for shear connector fatigue damage calculation in timber–concrete composites and enabling remaining life prediction for similar composite beam connectors. Finite element simulations of push-out specimens showed high consistency between calculated and experimental fatigue life/damage results, validating the conclusions.